Woodstock in Timbuktu - Die Kunst des Widerstands - von Trotha, Desiree (Germany, 2011)
Each year, a music festival takes place in the Sahara - an event which is rooted in an ancient nomadic tradition. The festival is the ideal platform for encountering the Kel Tamasheq (Touareg) people and for witnessing their inspiring cultural aliveness. But because of the increasing challenges of globalization, their ancient nomadic traditions are now being threatened. The legendary Saharan people choose to fight back through their music.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films